The Readiness of Village Unit Cooperative in Facing Economic Competition and Globalization - Suratno Suratno; Deny Denmar; Bagus Shandy Narmaditya (Universitas Negeri Surabaya, 2021)
This study aims to investigate the continuance of village unit cooperative, the management, and preparation in facing business competition and globalization. This study employed a qualitative method with a phenomenological approach to gain an understanding of the phenomenon. Three village unit cooperatives were involved as a research subject in the area of oil palm plantations in Muaro of Jambi municipalities. The findings indicate that the village unit cooperative has been able to provide better prosperity for its members. Second, the village unit cooperative does not have a more advanced and modern business plan to compete in the current era. However, the business undertaken is a monopoly that makes it village unit cooperatives difficult to compete with other parties.